(untitled) (Journal of Nuclear Technology in Applied Science, 2022)
Radon concentration at Tanis, Sharqai, Egypt, was measured at the site as well as at the laboratory using a sealed Can-technique equipped CR-39 detector which was calibrated in advance. In situ measured radon concentration ranged from 72 ± 9 Bq m-3 to 144 ± 16 Bq m-3, while the equilibrium radon concentration of 20 soil samples collected from the same sites were ranged from 88 ± 12 Bq m-3 to 226 ± 36 Bq m-3 at the laboratory. The average radon concentration is less than the recommended value by ICRP of 300 Bq m-3 but it is higher than the recommended value by WHO of 100 Bq m-3. The radon exhalation rate was ranged from (24 ± 3 to 61 ± 10 10-4) Bq m-2 s-1. It shows a good correlation with the radium content of a linear correlation factor of R = 0.97, which implies, the radium content is a useful index for radon parameters. Moreover, the radiation dose was calculated using radon concentration at sites and its value was ranged from 0.40 ± 0.05 to 0.79 ± 0.09 mSv y-1 for workers and from 0.054 ± 0.007 to 0.108 ± 0.012 mSv y-1 for visitors. From the obtained results, we assure there is no radiation health hazard from visiting the studied archaeological site.